Towards a Conceptual Framework of IT Operating Model and its Implications for Emerging Practices in Information Technology - Durga Das Mishra; S. Vijayakumar Bharathi (Australasian Accounting, Business and Finance Journal, 2023)
This paper is to establish a fit-for-purpose conceptual framework for the IT Operating model to handle emerging requirements in IT. Currently, there is no standard one size fits all kind of Operating Model. This paper brings a flexible IT Operating model to address emerging requirements. We examined today's various IT operating models suggested by Institutions and experts. Based on our study, we have proposed a conceptual framework for the IT Operating Model by carefully analysing the dimensions and mapping them to elements of IT Strategy and Operations discussed in this paper, giving an adaptive framework that can address various requirements. Our research shows a dearth of consistent framework and definition of an IT Operating Model. Hence, we see many facets of the operating model of organizations. Research, Advisory, and Consulting firms have given definitions and articulated the IT operating model to resolve this challenge. However, they need to be more consistent and address diverse requirements. This paper introduces a conceptual framework of the operating model to address the requirements of digital technology-related disruptions. This paper extends the existing body of knowledge around emerging IT Operating Models, and enhances it to create a conceptual framework. In doing this, we have also tried leveraging the existing knowledge body.
Keywords: Operating Model; Innovation; DDDD IT Framework; Strategy and Operations; Digital Disruption